Development of a tailored strategy to improve postpartum hemorrhage guideline adherence - Suzan M. de Visser; Mallory D. Woiski; Richard P. Grol; Frank P. H. A. Vandenbussche; Marlies E. J. L. Hulscher; Hubertina C. J. Scheepers; Rosella P. M. G. Hermens (BMC, 2018)
Abstract Background Despite the introduction of evidence based guidelines and practical courses, the incidence of postpartum hemorrhage shows an increasing trend in developed countries. Substandard care is often found, which implies an inadequate implementation in high resource countries. We aimed to reduce the gap between evidence-based guidelines and clinical application, by developing a strategy, tailored to current barriers for implementation. Methods The development of the implementation strategy consisted of three phases, supervised by a multidisciplinary expert panel. In the first phase a framework of the strategy was created, based on barriers to optimal adherence identified among professionals and patients together with evidence on effectiveness of strategies found in literature. In the second phase, the tools within the framework were developed, leading to a first draft. In the third phase the strategy was evaluated among professionals and patients. The professionals were asked to give written feedback on tool contents, clinical usability and inconsistencies with current evidence care. Patients evaluated the tools on content and usability. Based on the feedback of both professionals and patients the tools were adjusted. Results We developed a tailored strategy to improve guideline adherence, covering the trajectory of the third trimester of pregnancy till the end of the delivery. The strategy, directed at professionals, comprehending three stop moments includes a risk assessment checklist, care bundle and time-out procedure. As patient empowerment tools, a patient passport and a website with patient information was developed. The evaluation among the expert panel showed all professionals to be satisfied with the content and usability and no discrepancies or inconsistencies with current evidence was found. Patients' evaluation revealed that the information they received through the tools was incomplete. The tools were adjusted accordingly to the missing information. Conclusion A usable, tailored strategy to implement PPH guidelines and practical courses was developed. The next step is the evaluation of the strategy in a feasibility trial. Trial registration Clinical trial registration: The Fluxim study, registration number: NCT00928863.